2018
DOI: 10.21272/jnep.10(2).02036
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Undoped and (Al, In) Doped ZnO Thin Films Prepared by Ultrasonic Spray Pyrolysis for Solar Cell Applications

Abstract: Zinc oxide (ZnO) is an n-type semiconductor with a large optical gap (3.4 eV) belonging to the transparent conductive oxides family (TCO). Strongly present as optical window in the chalcopyrite based structures CIGS and CIS. The structural, morphological, optical and electrical properties of ZnO thin films deposited onto glass substrates by ultrasonic spray pyrolysis (USP) technique have been investigated. For comparison and a better understanding of physical properties of undoped and (Al, In) doped ZnO thin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…B-doped ZnO, Al-doped ZnO, and Ga-doped ZnO thin films are found to have transmittance values close to that of undoped ZnO, which is in agreement with our previous published work on B-doped ZnO thin films [27]. The measured transmittance of Al-doped ZnO thin films is in good agreement with the findings reported in [16,20]. The obtained transmittance of Ga-doped ZnO thin films is consistent with previously reported findings [18,37].…”
Section: Uv-vis Spectroscopysupporting
confidence: 92%
See 2 more Smart Citations
“…B-doped ZnO, Al-doped ZnO, and Ga-doped ZnO thin films are found to have transmittance values close to that of undoped ZnO, which is in agreement with our previous published work on B-doped ZnO thin films [27]. The measured transmittance of Al-doped ZnO thin films is in good agreement with the findings reported in [16,20]. The obtained transmittance of Ga-doped ZnO thin films is consistent with previously reported findings [18,37].…”
Section: Uv-vis Spectroscopysupporting
confidence: 92%
“…A further decrease of E g to 3.093 eV takes place as gallium is introduced into ZnO thin films in good agreement with [37]. On the other hand, the E g of the In-doped ZnO thin film is found to increase to 3.314 eV, a value that agrees well with the findings of [8], and to 3.369 eV when aluminum is introduced into the ZnO thin films, which is in excellent agreement with reported values of [16,17]. The fluctuations in the values of E g of doped ZnO thin films are expected and can be explained in terms of the variations in the values of crystallite sizes as the dopants are introduced in ZnO thin films, as will be demonstrated later by the X-ray diffraction patterns.…”
Section: Uv-vis Spectroscopysupporting
confidence: 90%
See 1 more Smart Citation
“…Several methods were adopted to synthesize undoped and doped ZnO thin films. Among reported methods, one finds laser deposition [14,15], sputtering [16], molecular beam epitaxy (MBE) [17], evaporation [18], chemical vapor deposition (CVD) [19], electrochemical deposition [20], doctor blade technique [21], chemical bath deposition (CBD) [22,23], chemical wet and dry (CWD) method [24], successive ionic layer adsorption and reaction (SILAR) method [25], spray pyrolysis [26][27][28][29], and sol-gel process including spin and dip-coating processes [30][31][32][33]. Due to its cheap manufacturing costs, effectiveness, simplicity, simple control of doping, broad area homogeneity, and crystalline consistency during the production of devices, the sol-gel dip-coating process is suited for thin film deposition [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the doping of Zinc Oxide (ZnO) with various metal elements such as gallium (Ga), indium (In), Tin (Sn), Lead (Pb), Iron (Fe), Nickel (Ni) and aluminum (Al) improve some of its properties [32][33][34][35][36][37][38]. Among them, aluminum (Al) is commonly used to form Al-doped ZnO (AZO) to improve the conductivity of zinc oxide [39]. In the present work, undoped and Al-doped ZnO thin lms were prepared by a dip-coating technique using different zinc and aluminum precursors and the effects of aluminum doping (concentration of Al: 0, 0.5, 1, 2, and 3 wt.%) on the structural, morphological, optical and electrical properties of ZnO thin lms were examined.…”
Section: Introductionmentioning
confidence: 99%